Factors associated with the maxillary third molar position after total arch distalization using a modified C‐palatal plate in adolescents. (2nd March 2021) - Kang, Hyojeong; Lee, Nam‐Ki; Kim, Jaehyun; Park, Jae Hyun; Kim, Yoonji; Kook, Yoon‐Ah
Abstract: Introduction: The purpose of this study was to evaluate the long‐term position of erupted third molars after maxillary total arch distalization using modified C‐palatal plates (MCPPs) in adolescents and to identify factors associated with these positions. Setting and Sample Population: Sixty‐two third molars (male: 20, female: 42) in Class II patients treated with MCPPs and thirty‐nine teeth for the Control group (male: 22, female: 17). Materials and methods: Samples were analyzed using panoramic radiographs taken initially (T0), after treatment (T1) and after >3 years retention (T2). Third molars were classified as downward (Group A, N = 31; males: 12, females: 19) and upward (Group B, N = 31; males: 8, females: 23) based on their vertical position after treatment. Analysis of variance and multiple logistic regression analysis were performed. Results: The vertical position of the third molars of Group A, Group B, and the Control showed a 2.2, 3.5 and 2.7 mm downward movement at T2. However, there was no difference in the amount of third molar eruption among the groups. Regarding factors affecting the vertical distance of the third molar, Age, C8‐OP, ∠8‐OP and D7‐T at the initial affected vertical position of the third molars after molar distalization ( P  < .05). Conclusions: Group A and B showed no difference in the third molar eruption during retention after total arch distalization. This study suggests that it might be unnecessary to extract the developing third molar before molar distalization in Class II adolescents.